SYSTEM OF RECORDS FOREIGN VISIT - LAVRINCIK, Jan; Milan, KLEMENT (Trends in education, 2009)
The paper describes development, control, possibilities improve, and practical application program: System of records foreign visit. It explains which parts consist of database software; the selection of programming language from the point of view compatibility, development, and future extended are emphasized. It information with hierarchy structure authorized process. The article is supplement about flow diagram, and examples of Visual Basic sources.
Keywords: Erasmus; Free mover; Mobility; foreign visit.